2021
DOI: 10.1080/21505594.2021.1995253
|View full text |Cite
|
Sign up to set email alerts
|

Global regulator DksA modulates virulence of Acinetobacter baumannii

Abstract: DksA with (p)ppGpp regulates a wide range of gene transcriptions during the stringent response. The aim of this study was to identify a DksA ortholog in Acinetobacter baumannii and clarify the roles of DksA in bacterial physiology and virulence. The ∆ dksA mutant and its complemented strains were constructed using A. baumannii ATCC 17978. The AlS_0248 in A. baumannii ATCC 17978 was identified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The present study demonstrated that ∆ dksA mutants of clinical 1656-2 exhibited more morphological heterogeneity than the WT strain. Previous studies have reported that ∆ dksA mutant and (p)ppGpp-deficient mutant strains exhibited more morphological heterogeneity than the WT A. baumannii ATCC 17978 strain [ 20 , 25 ]. The (p)ppGpp-deficient and ∆ dksA mutants in E. coli also exhibited a more filamentous morphology than the WT strain [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that ∆ dksA mutants of clinical 1656-2 exhibited more morphological heterogeneity than the WT strain. Previous studies have reported that ∆ dksA mutant and (p)ppGpp-deficient mutant strains exhibited more morphological heterogeneity than the WT A. baumannii ATCC 17978 strain [ 20 , 25 ]. The (p)ppGpp-deficient and ∆ dksA mutants in E. coli also exhibited a more filamentous morphology than the WT strain [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the earliest research topics in multimodal machine learning (Zhang et al 2020). Transformers have been widely used in multimodal tasks such as Visual-Language Pre-training (Kim et al 2021;Li et al 2021) and Multimodal Named Entity Recognition (Yu et al 2020;Sun et al 2021) because they can mine the internal relationships among long sequences via self-attention mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…Transformer's (Vaswani et al 2017) powerful feature extraction capability results in the excellent performance of the same model across multiple modalities. Recent studies using the Transformer architecture on multimodal tasks have yielded promising results (Kim et al 2021;Li et al 2021;Sun et al 2021). We reference the advanced multimodal method in CV and NLP, using Transformer to combine complementary information from spectral and photometric images.…”
Section: Introductionmentioning
confidence: 99%
“…DksA also plays a key role in the control of virulence-related genes. In some pathogenic bacteria ( e.g., Escherichia coli , H. ducreyi , P. aeruginosa , S. enterica , Vibrio cholerae and A. baumannii ) dksA mutants are less virulent than the wild type both in vitro and in vivo 18 , 20 25 .…”
Section: Introductionmentioning
confidence: 99%